Dynamical scalar hair formation around a Schwarzschild black hole - Benkel, Robert; Sotiriou, Thomas P.; Witek, Helvi (American Physical Society, 2016)
Scalar fields coupled to the Gauss-Bonnet invariant evade the known no-hair theorems and have nontrivial configurations around black holes. We focus on a scalar field that couples linearly to the Gauss-Bonnet invariant and hence exhibits shift symmetry. We study its dynamical evolution and the formation of scalar hair in a Schwarzschild background. We show that the evolution eventually settles to the known static hairy solutions in the appropriate limit.